Application of The Technology Acceptance Model in Measuring Customer Satisfaction and Loyalty - Tasrif, Muh; Agus Setiawan, Anton; Purwo Saputro, Edy; Kussudyarsana, Kussudyarsana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2023)
This study aims to investigate the influence of technology acceptance factors and website service quality in measuring customer satisfaction and loyalty for online shopping. This research was conducted in Mamuju, Indonesia. The sample was selected using accidental sampling involving 200 Shopee marketplace users. The data in this study were processed using structural Equation Molding (SEM) with partial least square alternative 3.0 (PLS). The results of this study indicate that the technology acceptance factor has a positive and significant effect on customer satisfaction, the technology acceptance factor has a positive and significant effect on customer loyalty, website service quality has a positive and significant effect on customer satisfaction, website service quality has a positive and significant effect on customer loyalty and Consumer satisfaction has a positive and significant influence on consumer loyalty as well as customer satisfaction also plays a moderating role in the technology acceptance factor on loyalty through customer satisfaction and website service quality on customer loyalty through customer satisfaction.